Sufism in the Perspective of Ibn Khaldun and Ibn Taimiyah: A Comparative Study - Rahmat Effendi (Tamaddun, 2021)
The discourse of Sufism in contemporary period has been widely practiced. Even so, Sufism which is understood by Muslims there is disorientation in understanding it, especially as a result of the influence of Ibn Taimiyah and Ibn Khaldun. With a theological-rationalist approach, both have criticized and reconstructed Sufism teachings at a level that is acceptable to Muslims. Both also explain the meaning of Sufism as far as they can reach. This article examines the comparative discourse on the concept of Sufism between Ibn Taimiyah and Ibn Khaldun. This research is library research using descriptive-analytical and comparative methods. Their thoughts on Sufism were dissected in depth which was then compared to find common ground for similarities and differences. The Sufism paradigm put forward by Ibn Taimiyah and Ibn Khaldun provides an overview at the theoretical and practical levels that can be explained rationally. That way Muslims are not polarized in understanding Sufism which seems to love the afterlife and leave the world. Finally, this research shows that Sufism can be practiced by Muslims in their respective capacities.  Wacana tasawuf pada masa kontemporer saat ini telah marak dilakukan. Meskipun begitu tasawuf yang dipahami oleh umat Islam terdapat disorientasi dalam memahaminya, terutama akibat dari pengaruh Ibn Taimiyah dan Ibn Khaldun. Dengan pendekatan teologis-rasionalis keduanya telah melakukan kritik dan rekonstruksi ajaran tasawuf dalam tataran yang dapat diterima oleh umat Islam. Keduanya juga menjelaskan makna tasawuf sejauh yang dapat mereka jangkau. Artikel ini mengkaji diskursus perbandingan konsep tasawuf antara Ibn Taimiyah dan Ibn Khaldun. Penelitian ini adalah studi pustaka (library research) dengan menggunakan metode deskriptif-analitis dan komparasi. Pemikiran keduanya atas tasawuf dibedah secara dalam yang kemudian dikomparasikan guna menemukan titik temu persamaan dan perbedaannya. Paradigma tasawuf yang dikemukakan oleh Ibn Taimiyah dan Ibn Khaldun memberikan gambaran dalam tataran teoritis dan praktis yang dapat dijelaskan secara rasional. Dengan begitu umat Islam tidak terpolarisasi dalam memahami tasawuf yang terkesan cinta akhirat dan meninggalkan dunia. Akhirnya penelitian ini menunjukkan bahwa tasawuf pada dasarnya dapat dipraktikkan oleh umat Islam dalam kapasitasnya masing-masing.